2010
DOI: 10.3324/haematol.2009.012864
|View full text |Cite
|
Sign up to set email alerts
|

Increased MYC gene copy number correlates with increased mRNA levels in diffuse large B-cell lymphoma

Abstract: BackgroundTranslocations involving the MYC gene and increased MYC mRNA levels are associated with poor outcome in diffuse large B-cell lymphoma. However, the presence of increased MYC gene copy number and/or polysomy of chromosome 8 have not been previously described. Design and MethodsUtilizing dual color chromogenic in situ hybridization, we investigated MYC gene copy and chromosome 8 centromere numbers in 52 cases of diffuse large B-cell lymphoma. Cases were divided into those with "increased" or "not incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 39 publications
2
67
2
Order By: Relevance
“…19,20 Second, the association between VpreB3 expression and a subset of DLBCL with c-MYC polysomy raises the possibility that, in a minority of cases, increased c-MYC copy number may partially recapitulate the genetic program of tumors with a c-MYC translocation. 33 Third, our inability to find a direct correlation between VpreB3 and c-Myc transcript abundance in tumors lacking c-MYC genetic abnormalities (Online Supplementary Figure S3) suggests that the expression of VpreB3 may not be directly regulated by the c-Myc protein itself but the result of a broader dysfunctional genetic program in tumors harboring a c-MYC aberration. Further studies are needed to delineate the molecular mechanisms underlying the expression of VpreB3 in these tumors.…”
Section: Discussionmentioning
confidence: 82%
“…19,20 Second, the association between VpreB3 expression and a subset of DLBCL with c-MYC polysomy raises the possibility that, in a minority of cases, increased c-MYC copy number may partially recapitulate the genetic program of tumors with a c-MYC translocation. 33 Third, our inability to find a direct correlation between VpreB3 and c-Myc transcript abundance in tumors lacking c-MYC genetic abnormalities (Online Supplementary Figure S3) suggests that the expression of VpreB3 may not be directly regulated by the c-Myc protein itself but the result of a broader dysfunctional genetic program in tumors harboring a c-MYC aberration. Further studies are needed to delineate the molecular mechanisms underlying the expression of VpreB3 in these tumors.…”
Section: Discussionmentioning
confidence: 82%
“…11,19 Furthermore, studies using gene set enrichment analysis showed that high MYC 20,21 Other studies have demonstrated higher levels of MYC mRNA in DLBCL with increased gene copy numbers and correlated these results with an unfavorable prognosis. 22,23 In brief, all these studies indicate the importance of identifying MYC genetic changes in DLBCL. However, most of these studies evaluated only the impact of isolated changes of the MYC gene, were performed in small series of patients, or considered patients treated with CHOP and R-CHOP chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these studies evaluated only the impact of isolated changes of the MYC gene, were performed in small series of patients, or considered patients treated with CHOP and R-CHOP chemotherapy. 15,22,23 At the protein level, high expression of MYC detected by immunohistochemistry may be useful to identify cases with MYC translocations. 20,24,25 In this study we investigated the clinical impact of the spectrum of MYC gene alterations and MYC protein expression in DLBCL in comparison to that of other gene alterations.…”
Section: Introductionmentioning
confidence: 99%
“…52,53 However, this has not been consistently shown to be associated with increased MYC protein expression or an inferior clinical outcome. 17,[53][54][55][56][57][58] Other factors can affect MYC levels without directly altering the integrity or location of the MYC locus. Many signaling pathways, including BCR and NF-kB signaling, can lead to increased transcription of MYC through direct and indirect interactions at the MYC promoter as reviewed by Wierstra and Alves.…”
Section: 44mentioning
confidence: 99%